2020
DOI: 10.1128/jvi.01105-20
|View full text |Cite
|
Sign up to set email alerts
|

Critical Residues and Contacts within Domain IV of Autographa californica Multiple Nucleopolyhedrovirus GP64 Contribute to Its Refolding during Membrane Fusion

Abstract: Autographa californica multiple nucleopolyhedrovirus (AcMNPV) GP64 is a class III viral fusion protein that mediates low-pH triggered membrane fusion during virus entry. Although the structure of GP64 in a postfusion conformation has been solved, its prefusion structure and the mechanism of how the protein refolds to execute fusion are unknown. In postfusion structure, GP64 is composed of five domains (domain I-V). Domain IV (374-407 aa) contains two loops (loop 1 and loop 2) that form a hydrophobic pocket at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
1
0
0
Order By: Relevance
“…Likewise, we previously showed that BV-cOVA treatment with Mab V1 antibody blocks anti-OVA CTL generation, confirming that GP64 is required for BV processing in DCs [13]. This result is in line with previous reports showing that GP64 mediates virus nucleocapsid release from endosomes, fusing the viral envelopes with the endosomal membrane after the internalization of BVs by both insects and mammalian cells [17,34,35].…”
Section: Discussionsupporting
confidence: 91%
“…Likewise, we previously showed that BV-cOVA treatment with Mab V1 antibody blocks anti-OVA CTL generation, confirming that GP64 is required for BV processing in DCs [13]. This result is in line with previous reports showing that GP64 mediates virus nucleocapsid release from endosomes, fusing the viral envelopes with the endosomal membrane after the internalization of BVs by both insects and mammalian cells [17,34,35].…”
Section: Discussionsupporting
confidence: 91%